Peran persepsi keterlibatan orangtua dan peran sosial guru dengan efikasi diri akademis siswa dalam pembelajaran online di masa pandemi - Dewi Arum Widhiyanti Metra Putri; Rahma Widyana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aimed to determine: 1) The correlation between perceptions on parental involvement and students' academic self-efficacy in online learning; 2) The correlation between perceptions on teacher’s social role and students' academic self-efficacy in online learning; 3) The correlation between perceptions on parental involvement and perceptions on teacher’s social role with students' academic self-efficacy in online learning. The subjects were 900 senior and junior high school students in Buleleng Regency, Bali who took online learning during the Covid-19 pandemic. The data collection tools used were scale of student's academic self-efficacy, scale of perception on parental involvement, and scale of the perception on teacher's social role. The simple regression technique was used to analyze the first and second hypotheses, while the multiple regression technique was used to tests the third hypothesis. The results indicated that; 1) There was a positive relationship between perceptions on parental involvement with students' academic self-efficacy in online learning during pandemic period, 2) there was a positive relationship between perceptions on teacher’s the social role and students' academic self-efficacy 3) there was a positive relationship between perceptions on parental involvement and perceptions on teacher’s social role with students' academic self-efficacy in online learning during pandemic.